2014
DOI: 10.1371/journal.pone.0097800
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Residency and Urbanicity on Haemophilus influenzae Type b and Pneumococcal Immunization in Shanghai Children: A Retrospective Cohort Study

Abstract: Background Haemophilus influenzae type b (Hib) vaccine and pneumococcal conjugate vaccine (PCV) are relatively expensive, newly introduced vaccines in China. This study evaluates the impact of residency and urbanicity on Hib vaccine and PCV coverage for children aged 2 to 7 years living in Shanghai, China, in August 2012.MethodsIn this exploratory cohort study, a sample of children aged 2 to 7 years, all of whom were eligible to have received the complete series of Hib vaccine and PCV, was obtained from the Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 17 publications
2
37
0
Order By: Relevance
“…One study performed in 2014 in Shanghai showed a PCV vaccine coverage of 11.4% from 28 141 abstracted pediatric records. 22 In the present study, a total of five serotypes were identified among 12 S. pneumoniae isolates. There were four isolates of serotype 19F, three isolates of 23F, two isolates each of 19A and 14, and one isolate of 6A.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…One study performed in 2014 in Shanghai showed a PCV vaccine coverage of 11.4% from 28 141 abstracted pediatric records. 22 In the present study, a total of five serotypes were identified among 12 S. pneumoniae isolates. There were four isolates of serotype 19F, three isolates of 23F, two isolates each of 19A and 14, and one isolate of 6A.…”
Section: Discussionmentioning
confidence: 62%
“…One key contributing factor is that a meningococcal vaccine has been part of the National Immunization Program (NIP) since the 1980s; the coverage of group A meningococcal polysaccharide reported in 2012 was 91.22%. 21 The Hib vaccine has been in use since the 1990s with a coverage of 50.9%, 22 even though it has not been included in the NIP. The other key factor is the high rate of antimicrobial drug use in clinical practice in China.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have found that disparities between non-locals and locals are greater in regards to non-EPI vaccines than EPI vaccines. In a previous analysis of children <8 years of age living in Shanghai, we found that the coverage of DTP, an EPI vaccine, was similar in locals and non-locals, but there was substantially lower coverage of two non-EPI vaccines (PCV7 and a Haemophilus influenzae type b vaccine) among non-locals compared to locals [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…56 Another example comes from the study by MacDonald et al where they assess, through a postal questionnaire, the reasons for no vaccination, or partial immunization, in children 2 y old during the period May 2008-April 2009 in Edmonton, Canada. 48 The obtained results show that concerns about vaccine safety, lack of awareness about disease severity and susceptibility and lack of trust in Underimmunized cluster were in low publicfunded areas Wagner 131…”
Section: Characteristics Of Vaccines Refusers and Vaccines Recipientsmentioning
confidence: 89%
“…In this review, we synthetized results from 13 studies. [119][120][121][122][123][124][125][126][127][128][129][130][131] Eccles et al, using a geographical visualization method and IIS, assessed how geographical distribution of those who refuse vaccine had changed during a certain period and over time, identifying specific areas of non-vaccinated. 125 This geographical distribution has high public health impact, both to identify areas with health systems or ethnic-religious barriers and to identify areas with sanitary issues.…”
Section: Geographical Distribution Challenges and Barriers And Clustmentioning
confidence: 99%